Quasinormal modes of black holes in f(Q) gravity - Gogoi, Dhruba Jyoti; Övgün, Ali; Koussour, M. (Springer, 2023)
In this work, we have studied the quasinormal modes of a black hole in a model of the type f(Q)Sigma nin f(Q) gravity by using a recently introduced method known as Bernstein spectral method and confirmed the validity of the method with the help of well known Pade averaged higher order WKB approximation method. Here we have considered scalar perturbation and electromagnetic perturbation in the black hole spacetime and obtained the corresponding quasinormal modes. We see that for a non-vanishing nonmetricity scalar Q0, quasinormal frequencies in scalar perturbation are greater than those in electromagnetic perturbation scenarios. On the other hand, the damping rate of gravitational waves is higher for electromagnetic perturbation. To confirm the quasinormal mode behaviour, we have also investigated the time domain profiles for both types of perturbations.